Getting started with open VMS system management - Miller, David Donald (Boston : Digital Press, 2003)
Getting Started with OpenVMS System Management gives new VMS system managers a jumpstart in managing this powerful and reliable operating system. Dave Miller describes the essentials of what an OpenVMS System Manager will have to manage. He defines areas of OpenVMS System Management and describes why each is important and how it fits into the larger management task. Even though some OpenVMS management concepts are unique (for instance quotas), many concepts (such as account creation) have counterparts in UNIX and Windows NT. So, wherever possible, Miller points out to his readers the parallel to other systems. The book is intended as a precursor to Baldwin's OpenVMS System Management Guide and various OpenVMS documents. Thus it refers the reader to other books for the detailed management steps. Getting Started with OpenVMS System Management is a great introduction to the material Steve Hoffman and Dave Miller are revising for the OpenVMS System Management Guide, 2E. Permits experienced system managers to begin managing OpenVMS more quickly Dovetails with other Digital Press publications for easier reference by the OpenVMS manager Points you in the right direction for the complete documentation on each issue BONUS FEATURE! Includes excerpts from five key DP OpenVMS books.
1. Introduction -- 2. Booting and startup script -- 3. Licenses -- 4. User accounts, login, and accounting -- 5. Queues -- 6. Backup -- 7. System monitoring and performance management -- 8. Security -- 9. Network -- 10. Clusters -- Bibliography -- Appendixes: -- A. The user environment -- B. VMS and the Web -- C. Assessing OpenVMS and Linux: The right tool for the right job -- D. Memory management system services -- E. Symbols, data, and expressions.
Includes index.
Keywords: Operating systems (Computers).; OpenVMS; Electronic books